2022
DOI: 10.3390/ijms23063114
|View full text |Cite
|
Sign up to set email alerts
|

Type I–IV Halogen⋯Halogen Interactions: A Comparative Theoretical Study in Halobenzene⋯Halobenzene Homodimers

Abstract: In the current study, unexplored type IV halogen⋯halogen interaction was thoroughly elucidated, for the first time, and compared to the well-established types I–III interactions by means of the second-order Møller–Plesset (MP2) method. For this aim, the halobenzene⋯halobenzene homodimers (where halogen = Cl, Br, and I) were designed into four different types, parodying the considered interactions. From the energetic perspective, the preference of scouted homodimers was ascribed to type II interactions (i.e., h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 75 publications
(97 reference statements)
0
17
0
Order By: Relevance
“…For example, Ibrahim and coworkers showed that small negative interaction energies can be calculated when two molecules were oriented so that their positively charged σ or π-holes approached one another. 60,61 However, it is unclear if these geometries represented true minima as the orientations were rigidly enforced. SAPT partitioning offered small negative electrostatic components, consistent with the finding present above.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ibrahim and coworkers showed that small negative interaction energies can be calculated when two molecules were oriented so that their positively charged σ or π-holes approached one another. 60,61 However, it is unclear if these geometries represented true minima as the orientations were rigidly enforced. SAPT partitioning offered small negative electrostatic components, consistent with the finding present above.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the Lewis basicity effect was inspected by employing PoCs of −0.25 and −0.50 au on the SF 4 and SeF 4 monomers through three different sites, namely the σ- and lp-holes. In accordance, the enumerated stabilization energy ( E stabilization ) was quantified within the chalcogen σ- and lp-hole···PoC distance scope of 2.5–5.0 Å through a 0.1 Å step size using the following equation ,, E normals normalt normala normalb normali normall normali normalz normala normalt normali normalo normaln = E σ .25em normala normaln normald .25em normall normalp normalh normalo normall normale normalb normale normala normalr normali normaln normalg .25em normalm normalo normall normale normalc normalu normall normale · · · normalP normalo normalC E σ .25em normala normaln normald .25em normall normalp normalh normalo normall normale normalb normale normala normalr normali normaln normalg .25em normalm normalo normall normale normalc normalu normall normale …”
Section: Methodsmentioning
confidence: 99%
“…To electrostatically investigate to what extent the SF 4 and SeF 4 molecules could favorably form chalcogen σ– and lp–hole site-based interactions, the point-of-charge (PoC) approach was fulfilled. Thus, the Lewis basicity effect was inspected by employing PoCs of −0.25 and −0.50 au on the SF 4 and SeF 4 monomers through three different sites, namely the σ- and lp-holes.…”
Section: Methodsmentioning
confidence: 99%
“…The highest stabilizing energy is obtained when the θ H and θ L angles are 180°and 90°respectively, which is followed by θ H = θ L = 90°. The trend is very similar to the homo-halogen••• halogen interactions reported by Ibrahim et al 53 It may be noted that, according to their calculation, the interaction energies for the Ph−Cl•••Cl−Ph and Ph−Br•••Br−Ph interactions with θ X = 180°and 90°geometry are −1.32 and −1.80 kcal/mol, respectively, at the MP2/aug-cc-pVDZ level of theory. The interaction for the θ H = 180°and θ L = 90°geometry is slightly more stabilizing compared to that for θ H = 90°and θ L = 180°in the case of Br•••Cl interactions.…”
Section: Plots Of % Populations Vsmentioning
confidence: 99%